Odpowiedzi

2010-04-13T17:49:56+02:00
A) x=4,5
b)x=9
c)x=-3
d)x=-1,5
e)x=-2
f)t=-7
g)x=10
h)0=0
i)x= - 17/5
6 3 6
2010-04-13T17:52:25+02:00
A) 10-3=2x
7=2x /: 2
x=4,5
b) 2x+x=7+2
3x=9 / :3
x=3
c) 10-4=-2x
6=-2x /: (-2)
x=-3
d)-2x +1 = 4
-2x=3 // : -2
x=-1.5
e)2x +2 =x
x=-2
f)) 2t-(3t+1)=6
2t -3t -1 =6
-t=5 //: -1
t=-5
g)-(4+x)=2(3-x)
-4 -x=6-2x
x=10
h)3(y+6)-y=2(y+9)
3y +18-y= 2y-18
0 = 32
i)(x-7)-2(3x+5)=3
x-7-6x-10=3
5x=20 // :5
x=4
5 4 5
Najlepsza Odpowiedź!
2010-04-13T17:58:04+02:00
A)-3=2x-10/+10
7=2x/ :2
x=3.5
b)2x-2=7-x/+2
2x=9 - x/ +x
3x=9/:3
x=3
c) 10=4-2x/-4
6=-2x/:(-2)
-3=x
d) -(2x-1)=4
-2x +1= 4/-1
-2x = 3/:(-2)
x= -1.5
e) 2(x+1)=x
2x+2=x/-2x
-2=x
g) -(4+x)=2(3-x)
-4-x=6-2x/+2x
-4 +x=6/+4
x=10
h) 3(y+6)-y=2(y+9)
3y+18-y=2y+18
2y +18= 2y+18
0=0
i) (x-7)-2(3x+5)=3
(x-7)-6x-10=3/+10+7
x-6x=20
-5x=20/:(-5)
x=-4
a w podpunkcie C nie powinno być 10=4-2x /+4 ??